STUDENTS’ ERRORS IN CHANGING NOUNS INTO ADJECTIVES - Nita Ria (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The main objective of this research was to investigate the errors or mistakes students made in changing nouns into adjectices. The population of this research was the seventh grade students of one private junior high school in Palembang in the academic year of 2016-2017. The sample of this study was 36 students who were selected randomly by using cluster sampling. To collect the data, a written test was given to the sample. The results of the test were analyzed descriptively.The findings showed that the students made errors in changing nouns into adjectives with the suffixes “-less”(58.3%), “-ful” (66.6%), “-able” (61.1%) and “-y” (55.5%) and they made mistake with the suffixes “-ly” (52.7%) of the incorrect answers. It is expected that the results of this research can be used as consideration for the English teachers in their teaching, especially the one focusing on changing nouns into adjectives.Keywords: error, mistake, adjectives, suffixes